1993
DOI: 10.1021/ac00049a003
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced conformational changes in proteins studied by electrospray ionization mass spectrometry

Abstract: A simple and effective device for investigating heat-induced denaturation of proteins by electrospray ionization mass spectrometry is described. Results are presented for the denaturation as a function of temperature and solution pH of bovine ubiquitin and bovine cytochrome c. These results are in concert with and extend the earlier results of LeBlanc et al. (Org. Mass Spectrom. 1991, 26, 831). The cooperative effects of pH and temperature on the denaturation of ubiquitin and cytochrome c were investigated. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
209
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(232 citation statements)
references
References 10 publications
21
209
0
Order By: Relevance
“…To date, the relationship between ESI-MS charge state distributions (i.e., protein conformation in the gas phase) has correlated well with the conformational properties of proteins in solution, thus supporting the notion that protein structure in the solution phase can be retained after ionization and, for some time, into the gas phase [23,24]. But what about a more realistic situation in which a protein could populate a number of conformational states simultaneously?…”
Section: What Can We Learn About Protein Conformers?mentioning
confidence: 79%
See 1 more Smart Citation
“…To date, the relationship between ESI-MS charge state distributions (i.e., protein conformation in the gas phase) has correlated well with the conformational properties of proteins in solution, thus supporting the notion that protein structure in the solution phase can be retained after ionization and, for some time, into the gas phase [23,24]. But what about a more realistic situation in which a protein could populate a number of conformational states simultaneously?…”
Section: What Can We Learn About Protein Conformers?mentioning
confidence: 79%
“…Early ESI-MS experiments illustrated that the m/z charge state distribution of a protein depended on its folded state, with a more folded protein having a narrower charge state distribution with fewer charges on average than the same protein analyzed under alternative solution conditions which favor a less folded conformation [23]. To date, the relationship between ESI-MS charge state distributions (i.e., protein conformation in the gas phase) has correlated well with the conformational properties of proteins in solution, thus supporting the notion that protein structure in the solution phase can be retained after ionization and, for some time, into the gas phase [23,24].…”
Section: What Can We Learn About Protein Conformers?mentioning
confidence: 99%
“…It is accepted that the shape of the charged distribution does mainly depend on the availability of the various chargeable basic sites (Arg, Lys, His and the N-terminus) [8], and thus to the tertiary structure of the protein (i. e. in a highly folded protein few basic sites will be available, however, in a fully unfolded state all basic sites should be accessible) [9]. This effect on the charge state distribution of protein has been verified studying the influence of acids [10], temperature [11] or solvents [12]. However, recently it has also been shown that proteins themselves can have an important influence on the response of other proteins [13].…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, soon after the introduction of MALDI and ESI, these ionization methods were already used for the study of intact proteins and noncovalent protein complexes (Ganem, Li, & Henion, 1991;Miranker et al, 1993;Mirza, Cohen, & Chait, 1993;. In particular, ESI is well suited to detect and investigate non-covalent complexes by transferring whole intact assemblies into the vacuum inside the mass spectrometer.…”
Section: Introductionmentioning
confidence: 99%